النظام القانوني للمؤسسات العقابية في الجزائر - بالخير إنتصار (جامعة الوادي University of El Oued, 2025)
شهدت المؤسسات العقابية في الجزائر تحولات وتحديات كبيرة في إطار قانوني يهدف إلى تحقيق التوازن بين العقاب وإعادة التأهيل؛ وتسعى هذه الجهود إلى مواءمة المعايير الدولية المتعلقة بمعاملة السجناء وصون حقوقهم. ونتيجة لذلك، اعتمدت الجزائر تشريعات تنظم السجون وتعزز إعادة الإدماج الاجتماعي للنزلاء، بهدف إرساء مبادئ وقواعد سياسة عدالة جنائية قائمة على فكرة الردع الاجتماعي. وتسعى هذه السياسة إلى تطبيق العقاب كوسيلة لحماية المجتمع، مع التركيز على إعادة تأهيل السجناء وإعادة إدماجهم؛ وعليه، فإن التنظيم السليم للمؤسسات العقابية، سواء من حيث هيكلها أو طبيعة أنشطتها التأهيلية، يمكن أن يوجه العقاب ليصبح وسيلة لإعادة التأهيل بدلاً من مجرد أداة للردع. Pinal institutions in Algeria have witnessed significant changes and challenges within a legal framework aimed at achieving a balance between punishment and rehabilitation; These efforts seek to align with international standards regarding the treatment of prisoners and the safeguarding of their rights, Consequently, Algeria has adopted legislation regulating prisons and promoting the social reintegration of inmates, aiming to establish principles and rules of a criminal justice policy based on the idea of social deterrence, This policy seeks to apply punishment as means to protect society, while emphasizing the re-education and reintegration of prisoners; Accordingly, the proper organization of penal institutions, both in terms of their structure and the nature of their rehabilitative activities, can guide punishment towards becoming a means of rehabilitation rather than merely a tool for deterrence.
جريمة وأمن
Keywords: المؤسسة العقابية، السجناء، موظفو إعادة التأهيل، العقوبة، إعادة التأهيل.; Penal institution; Prisoners; Rehabilitation Staff; Punishment; Rehabilitation